PENGARUH BUDAYA ORGANISASI, KEPUASAN KERJA, DAN SEMANGAT KERJA TERHADAP KINERJA GURU PADA MTs AL-HUDA PEKANBARU - Hendra, Teguh (Eko dan Bisnis: Riau Economic and Business Review, 2016)
The purpose of this research is to know and understand the influence of organizational culture on teacher performance, to know and understand the effect of job satisfaction on the performance of teachers, to know and understand the influence morale on teacher performance and to know and understand the influence of organization culture, job satisfaction, and excitement working simultaneously (simultan) on teacher performance.The result of the analysis show that the F test organizational culture, job satisfaction, and morale simultaneously positive and significant impact on the performance of teachers at MTs Al-Huda Pekanbaru. The result of the analysis of the test T is a) culture organizatitons are not positive and no significant effect on the performance of teachers, b) job satisfaction positive and significant effect on the performance of teachers, c) morale and no significant positive effect on theacher performance. Of the independents variabels suggest that any of the three independent variabels which have contributed the most effect on the performance of theachers is job satisfaction.Finally, the authors suggest to MTs Al-Huda Pekanbaru in order to enhance and support the performance of teachers at MTs Al-Huda Pekanbaru